2017
DOI: 10.21512/bbr.v8i1.1757
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Good Corporate Governance and Environmental Performance on Financial Performance of the Proper Listed Company on Indonesia Stock Exchange

Abstract: This research aimed to determine whether the environmental performance and Good Corporate Governance (GCG) mechanisms, such as managerial ownership, institutional ownership, the proportion of independent commissioners had effects of the audit committee on measured financial performance by using Return on Equity (ROE). This research population was manufacturing company listed on Indonesia Stock Exchange that participated in PROPER 2012PROPER /2013PROPER and 2013PROPER /2014. Based on the multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
3
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
3
10
3
13
Order By: Relevance
“…Based on the value of path coefficient, the results also prove empirically that the better implementation of GCG will improve company performance. The study results are supported by very many previous research results which generally stated that the implementation of GCG can improve the company performance, such as Andriana & Panggabean find that GCG mechanism simultaneously have significant effect on financial performance [13], Tornyeva & Theophilus show that GCG has positively associated with the financial performance [17], Fidanoski et al also show that GCG mechanism has positively related to the bank's profitability measures by ROA [18], and Mustapa, Rizad & Ghazali argue that GCG has related to firm performance [5], and Buallay et al show that GCG has positive impact on firm performance, and others [26]. Based on the results of interviews with the management of sharia banking, the implementation of GCG in terms of principles will be able to encourage the realization of good company performance as well.…”
Section: B the Influence Of The Implementation Of Good Corporatesupporting
confidence: 82%
See 1 more Smart Citation
“…Based on the value of path coefficient, the results also prove empirically that the better implementation of GCG will improve company performance. The study results are supported by very many previous research results which generally stated that the implementation of GCG can improve the company performance, such as Andriana & Panggabean find that GCG mechanism simultaneously have significant effect on financial performance [13], Tornyeva & Theophilus show that GCG has positively associated with the financial performance [17], Fidanoski et al also show that GCG mechanism has positively related to the bank's profitability measures by ROA [18], and Mustapa, Rizad & Ghazali argue that GCG has related to firm performance [5], and Buallay et al show that GCG has positive impact on firm performance, and others [26]. Based on the results of interviews with the management of sharia banking, the implementation of GCG in terms of principles will be able to encourage the realization of good company performance as well.…”
Section: B the Influence Of The Implementation Of Good Corporatesupporting
confidence: 82%
“…Good corporate governance can control management and risk so as to have positive and significant impact on organizational performance [12]. There are many other studies which have shown that implementation of GCG is able to contribute to improving company performance such as Andriana & Panggabean find that GCG mechanism simultaneously have significant effect on financial performance [13], Ahmed & Hamdan found a positive influence of CG mechanism on performance [14], Naimah & Hamidah show that CGG positively influence profitability [15], Rahnama & Jalili also show that CG Index significantly impacts on the company performance [16], Yesser et al show that CG mechanisms have significantly positive relationship with ROE [12]. There are many other investigations have found that GCG has positively associated with the financial performance [17], GCG has positively related to the bank's profitability measure by ROA [18], in generally GCG has positive impact on all the performance indicators of an organization [19], the other result show that GCG has relationship with bank performance [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies by Al-Haddad, Alzurqan, & Al-Sufy (2011), Sumarno, Widjaja, & Subandriah, (2016), Andriana & Panggabean (2017), and Mulyono, Suprapto, & Prihandoko (2018), support the argument that better corporate governance tends to have better performance, then there is a positive relationship between corporate governance and firm performance. Theoritically, Khan (2011) explained that corporate governance also enhances the long-term shareholder value by the process of accountability of managers and by enhances the firm's performance.…”
mentioning
confidence: 97%
“…Most studies in Indonesia analyzed corporate governance as an internal mechanism (Sumarno, Widjaja, & Subandriah, 2016;Andriana & Panggabean, 2017;Mulyono, Suprapto, & Prihandoko, 2018), then this study will give empirical evidence whether internal, external, or both mechanism that was implemented as a corporate governance mechanism in Indonesia using causality test. The causality test may predict causality between ownership and firm performance, whether ownership is causing firm performance, firm performance is causing ownership or both event, there is said to be a feedback relationship between ownership and firm performance.…”
mentioning
confidence: 99%
“…Berbagai penelitian telah dilakukan untuk membuktikan pengaruh GCG terhadap kinerja/nilai perusahaan. Penelitian yang dilakukan oleh Aggrawal (2013), Michelbelger (2017), Andriana (2017) yang menemukan bahwa GCG memiliki hubungan positif dengan nilai atau kinerja perusahaan. (Suntraruk, 2013) menemukan hubungan positif antara indeks GCG dengan kinerja perusahaan jangka panjang.…”
unclassified